قرآنی آیات اور جدید سائنسی علوم : ایک مطالعہ: A Study of Quranic Verses and Modern Sciences (Al-Qamar, 2021)
Qur'an is undoubtedly, a unique source of guidance and a complete code of conduct for religious as well as everyday life. The book invites both its followers, and the pagans to contemplate in the universe and embrace the eternal truth. Science is another name of human curiosity to find that truth. There are certain scientific terms which have been used for   layman and the scholars both. We study the natural phenomena with this terminology Including Biology, Physics, Chemistry, Geology, Astronomy, and many other branches of science. This article brings together the scientific definitions of these branches and the Qur'anic interpretations of certain branches of science.
Keywords: Quran; verses; Modern Sciences